Considerations for Use of Roundup® and Similar Products in the Home Landscape - Andrew W. MacRae; Marina D'Abreau (EDIS)
HS1171, a 4-page fact sheet by Andrew W. MacRae and Marina D’Abreau, describes the type of Roundup® products available to homeowners and provides tips to limit off-target movement of glyphosate products. Includes references. Published by the UF Department of Horticultural Sciences, May 2010.